PROGRAM APPLICATIONS PACKETS DASYLAB AND LABVIEW FOR NEEDS OF ACQUISITION SIGNALS - Pawel, PTAK (Trends in education, 2014)
Article discusses and compares possibility of signal acquisition and application programming procedures in conditioning signals from the sensors using software packages DasyLab and LabView. Described the phenomenon of signal acquisition and presents a programming environment DasyLab and LabView. Sample applications designed using these software packages are presented in the second part of article.
Keywords: signal acquisition; software packages.